2017
DOI: 10.1101/148981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Ras-like GTPase Rem2 is a potent endogenous inhibitor of calcium/calmodulin-dependent kinase II activity

Abstract: CaMKII is a well-characterized, abundant protein kinase that regulates a diverse set of functions in a tissue specific manner. For example, in heart muscle, CaMKII regulates Ca2+ homeostasis while in neurons CaMKII regulates activity-dependent dendritic remodeling and Long Term Potentiation (LTP), a biological correlate of learning and memory. Previously, we identified the noncanonical GTPase Rem2 as a critical regulator of dendrite branching and synapse formation in the vertebrate nervous system. Here, we rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…5). Therefore, we favor a model where Rem2 functions as a cytosolic signaling molecule to mediate changes in gene expression in the nucleus, perhaps by interacting with the CaMK signaling pathways [14, 64]. …”
Section: Resultsmentioning
confidence: 99%
“…5). Therefore, we favor a model where Rem2 functions as a cytosolic signaling molecule to mediate changes in gene expression in the nucleus, perhaps by interacting with the CaMK signaling pathways [14, 64]. …”
Section: Resultsmentioning
confidence: 99%
“…Rem2 is a noncanonical Ras-like GTPase, expressed throughout the cell ( Ghiretti and Paradis, 2011 ) and is unlikely to be regulated by its nucleotide binding state ( Correll et al, 2008 ) in contrast to canonical Ras family members. The mechanism by which Rem2 transduces signals is an open area of investigation, although it has been shown to associate with VGCC subunits ( Chen et al, 2005 ; Finlin et al, 2006 ; Finlin et al, 2005 ; Pang et al, 2010 ) and CaMKII ( Flynn et al, 2012 ; Royer et al, 2017 ). In addition, our previous studies demonstrated that Rem2 functions in a CaMK signaling pathway to regulate dendritic complexity ( Ghiretti et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of a number of ion channels, important for establishing neuronal excitability, are regulated by Rem2 signaling in an activity-dependent manner ( Kenny et al, 2017 ). We also recently demonstrated that Rem2 is a novel inhibitor of CaMKII catalytic activity ( Royer et al, 2017 ). Interestingly, CaMKII has been shown to modulate calcium channel function to alter intrinsic excitability ( Sahu et al, 2017 ; van Welie et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%